Recycled water: potential health risks from volatile compounds and the use of 1,4-dichlorobenzene as a treatment performance indicator - Rodriguez, C; Linge, Kathryn; Blair, P.; Busetti, Francesco; Devine, B.; Van Buynder, P.; Weinstein, P.; Cook, A. (IWA Publishing, 2011)
Characterisation of the concentrations and potential health risks of chemicals in recycled water is important if this source of water is to be safely used to supplement drinking water sources. This research was conducted to: (i) determine the concentration of volatile organic compounds (VOCs) in secondary treated effluent (STE) and, post-reverse osmosis (RO) treatment and to; (ii) assess the health risk associated with VOCs for indirect potable reuse (IPR). Samples were examined pre and post-RO in one full-scale and one pilot plant in Perth, Western Australia. Risk quotients (RQ) were estimated by expressing the maximum and median concentration as a function of the health value. Of 61 VOCs analysed over a period of three years, twenty one (21) were detected in STE, with 1,4-dichlorobenzene (94%); tetrachloroethene (88%); carbon disulfide (81%) and; chloromethane (58%) most commonly detected. Median concentrations for these compounds in STE ranged from 0.81 μg/L for 1,4-dichlorobenzene to 0.02 μg/L for carbon disulphide. After RO, twenty six (26) VOCs were detected, of which 1,4-dichlorobenzene (89%); acrylonitrile (83%) chloromethane (63%) and carbon disulfide (40%) were the more frequently detected. RQ(max) were all below health values in the STE and after RO. Median removal efficiency for RO was variable, ranging from −77% (dichlorodifluoromethane) to 91.2% (tetrachloroethene).The results indicate that despite the detection of VOCs in STE and after RO, their human health impact in IPR is negligible due to the low concentrations detected. The results indicate that 1,4-dichlorobenzene is a potential treatment chemical indicator for assessment of VOCs in IPR using RO treatment.